Apcin inhibits the growth and invasion of glioblastoma cells and improves glioma sensitivity to temozolomide - Yiming Ding (Taylor & Francis Group, 2021)
Glioblastoma (GBM) is the most common malignant primary brain tumor, and GBM patients have a poor overall prognosis. CDC20 expression is increased in a variety of tumors and associated with temozolomide (TMZ) resistance in glioma cells. Apcin specifically binds to CDC20 to inhibit APC/C-CDC20 interaction and exhibits antitumor properties. The purpose of this article was to assess whether apcin inhibits tumor growth in glioma cell lines and increases the sensitivity of GBM to TMZ. In this study, a series of biochemical assays, such as Cell Counting Kit-8 (CCK-8), wound healing, apoptosis and colony formation assays, were performed to determine the antitumor properties of apcin in glioma cells. GBM cell apoptosis was detected by western blotting analysis of related proteins. Apcin increased the sensitivity of glioma to TMZ, as confirmed by CCK-8 and western blotting analysis. The results showed that apcin significantly inhibited the proliferation of glioma cells in a time- and dose-dependent manner. The migration decreased with increasing apcin concentrations. Increased Bim expression indicated that apcin promotes the apoptosis of glioma cells. Furthermore, apcin improved glioma sensitivity to TMZ. The results showed that apcin can effectively inhibit GBM growth and improve TMZ sensitivity. Apcin has the potential to treat GBM and is expected to provide new ideas for individualized treatment.